(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The integration of electrical engineering and machine learning offers a novel approach to enhancing precision in food nutrient profiling, addressing the growing demand for accurate and real-time nutritional information. Traditional methods often fall short due to their complexity, time consumption, and high costs. This paper explores the synergy between advanced sensor technologies, such as spectroscopy and electrochemical sensors, and machine learning algorithms, including deep learning and reinforcement learning. The study demonstrates how hybrid models can improve the accuracy and efficiency of nutrient analysis by leveraging the strengths of both fields. Case studies highlight successful applications in predicting nutrient content in various food products, showcasing marked improvements in accuracy and processing time. The findings suggest that this integrated approach can significantly enhance the precision of food nutrient profiling, offering valuable implications for personalized nutrition and food safety. The paper concludes with a discussion on the potential challenges and future research directions, emphasizing the need for continued innovation in sensor technology and data analysis methods to fully realize the benefits of this interdisciplinary approach.